A high-performance lithium-sulfur battery

By using molybdenum disulfide particles coated with metal molybdenum nanoparticles on the lithium-sulfur battery separator, the problems of loss of active substances and low Coulomb efficiency caused by the polysulfide shuttle effect are solved, and the battery performance is improved.

CN119560730BActive Publication Date: 2025-03-28SICHUAN UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510111508.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-03-28
Estimated Expiration
2045-01-23

AI Technical Summary

Technical Problem

Lithium sulfur batteries have polysulfide shuttle effect, resulting in irreversible loss of active substances, low Coulomb efficiency and safety problems.

Method used

Molybdenum disulfide particles coated with metal molybdenum nanoparticles are used as the functional coating of the separator. The catalytic activity of the metal molybdenum nanoparticles accelerates the redox reaction of polysulfides, promotes their conversion to solid Li2S, improves the utilization rate of sulfur and inhibits the shuttle effect of polysulfides.

Benefits of technology

It effectively suppresses the shuttle effect of polysulfide, improves the Coulomb efficiency and cycling stability of the battery, enhances the conductivity and mechanical strength of the diaphragm, and improves the overall performance of lithium-sulfur batteries.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention belongs to the field of lithium-sulfur secondary batteries, and relates to a high-performance lithium-sulfur battery, including a sulfur-carbon positive electrode, a lithium negative electrode, an electrolyte and a separator, wherein the separator includes a base film and a functional coating coated on one or both sides of the base film, and the functional coating includes molybdenum disulfide particles coated with metal molybdenum nanoparticles. It is first proposed to apply molybdenum disulfide particles coated with metal molybdenum nanoparticles to the functional layer of the lithium-sulfur battery separator, which can not only effectively inhibit the shuttle effect of polysulfides, but also accelerate the redox reaction of polysulfides, promote their rapid conversion into solid Li2S, improve the utilization rate of sulfur, reduce the accumulation of intermediate products, and improve the coulomb efficiency and cycle stability of the battery; the combination of the two forms an efficient conductive network, significantly improves the conductivity, promotes the rapid transmission of electrons therein, and improves the rate performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of lithium-sulfur secondary batteries, and in particular relates to a high-performance lithium-sulfur battery. The lithium-sulfur battery uses a diaphragm comprising a functional coating, which not only effectively suppresses the shuttle effect of polysulfides, but also has a catalytic effect on polysulfides, promotes the catalytic conversion of polysulfides, and improves the utilization rate of positive electrode sulfur. Background Art

[0002] Electrochemical energy storage system is a key system for converting, storing and controlling renewable clean energy. It is used to realize the conversion between chemical energy and electrical energy, and requires characteristics such as safety, low cost, high efficiency and long life. Currently, lithium-ion batteries are widely used in commercial applications, which have the advantages of light weight, low self-discharge and no memory effect. With the continuous development of electric vehicles and electronic devices, people have put forward higher requirements for the energy density and specific energy of energy storage batteries. However, the energy density of lithium-ion batteries is currently low and can no longer meet people's long-term development needs. Therefore, it is necessary to develop new electrochemical energy storage systems with high specific capacity and high energy density.

[0003] Lithium-sulfur battery is a battery system that uses elemental sulfur as the positive electrode material and metallic lithium as the negative electrode material. It has attracted widespread attention due to its advantages such as low price, environmental friendliness and high specific capacity of elemental sulfur as the positive electrode material. Lithium-sulfur batteries still have problems such as low utilization rate of active sulfur, short cycle life and poor rate performance. In addition, soluble polysulfides will be formed when the sulfur positive electrode is discharged. A large amount of dissolved polysulfides will form a concentration difference between the positive and negative electrodes, and migrate to the negative electrode under the action of the concentration gradient, resulting in irreversible capacity loss of active substances; at the same time, some oligomeric reduction products will diffuse back to the positive electrode under the action of the concentration gradient for re-oxidation, thereby producing a "shuttle effect" to reduce the Coulomb efficiency, and due to the unevenness of the electrode surface, lithium dendrites may be generated, leading to safety problems. The shuttle effect will lead to irreversible loss of active materials. At the same time, since it is difficult for sulfur to completely complete the reaction and convert into the final product before and after the electrochemical reaction, it will lead to low coulombic efficiency. As the number of cycles increases, the available sulfur gradually decreases. In severe cases, it may cause overcharging of the lithium-sulfur battery, causing the capacity of the lithium-sulfur battery to decay, which directly leads to the loss of active materials in the lithium-sulfur battery and a decrease in coulombic efficiency.

[0004] In order to avoid short circuit caused by contact between the positive and negative electrodes, lithium-sulfur batteries are specially separated by a diaphragm. The diaphragm also provides a transmission channel for ion transmission in the electrolyte and has good permeability and physical flexibility. Modifying the diaphragm or preparing a separator to block polysulfides and promote lithium ion conduction has become a new research direction. Carbon materials can physically block polysulfides and improve the conductivity of the positive electrode side when used as diaphragm modification materials due to their advantages such as high conductivity, rich pore structure, and strong processing performance, showing excellent electrochemical properties. For example, CN112290162A discloses a cobalt-doped carbon nanotube composite diaphragm and a preparation method thereof, wherein g-C3N4, glucose and cobalt nitrate hexahydrate are mixed, ground and calcined to obtain cobalt-doped carbon nanotubes, the cobalt-doped carbon nanotubes are mixed with ethanol, stirred evenly and then filtered onto a polypropylene diaphragm, and dried to obtain a cobalt-doped carbon nanotube composite diaphragm; the large specific surface area of ​​the cobalt-doped carbon nanotubes prepared can effectively adsorb polysulfides generated during the charge and discharge process of lithium-sulfur batteries, and the high electronic conductivity of the carbon nanotubes can effectively compensate for the low electronic conductivity of the active substance sulfur; single-atom cobalt is evenly dispersed on the surface of the carbon nanotubes, and the high catalytic activity of the single atom can effectively enhance the kinetics of converting long-chain lithium polysulfide into short-chain lithium sulfide, improve the utilization rate of the active sulfur in the positive electrode, and thus further improve the electrochemical performance of the lithium-sulfur battery. CN114068935A discloses a highly active Mn / Co-N dual-site doped carbon material catalyst, which uses Co-doped MnO2 as an initiator for the polymerization of aniline monomers. During the polymerization of aniline monomers, more defective nitrogen atoms and spatially restricted sites can be formed on the polyaniline structure. These defects can absorb manganese ions (Mn 2+ ) and cobalt ions (Co 2+) is adsorbed on the polyaniline structure, and a stable active site is formed during the subsequent pyrolysis process. When this catalyst with high catalytic activity and high metal single atom loading is applied to a lithium-sulfur battery, it can reduce the reaction barrier of polysulfides and increase their reaction rate; limit the shuttling of polysulfides; and the highly conductive carrier can improve the utilization rate of sulfur and its discharge products. CN114976474A discloses a rare earth single atom material, which uses the prepared RE-NC as a diaphragm modification material for a lithium-sulfur battery, thereby improving the conductivity of the lithium-sulfur battery, and can not only catalyze the coordinated reaction regulation and accelerate the conversion of lithium polysulfide, but also help to inhibit the shuttling effect of lithium polysulfide and improve the utilization rate of sulfur active substances. CN117335094A discloses a method for preparing a high-entropy single-atom catalyst modified diaphragm, wherein different soluble metal salts and carbon nitrogen compounds are mixed and heat-treated to obtain a precursor, and then the metal atoms on the precursor are migrated to the nitrogen-doped carbon carrier by high-temperature argon treatment to obtain a high-entropy single-atom catalyst, which can be used as a modification material for the diaphragm in a lithium-sulfur battery. The wettability of the diaphragm to the electrolyte is greatly improved, the kinetics of the redox reaction of sulfur is accelerated, the shuttle effect is suppressed, and the transmission of lithium ions at the positive electrode / diaphragm reaction interface can be accelerated, so that the lithium-sulfur battery exhibits excellent cycle performance and rate performance. CN105977434A discloses a spherical hollow cerium oxide modified lithium-sulfur battery diaphragm, the modified diaphragm includes a diaphragm body, one side of the diaphragm body is coated with a modified coating, the modified coating contains spherical hollow cerium oxide, a conductive agent and an adhesive, the modified diaphragm can effectively block, adsorb and catalyze the polysulfides generated during the charge and discharge process, effectively suppress the shuttle effect of polysulfides, and thus improve the performance of lithium-sulfur batteries. However, the current modification of the diaphragm only blocks the polysulfide on the positive electrode side to reduce its transfer to the negative electrode. The carbon material as a conductive network can promote electron transfer and can also physically block the "shuttle effect" of polysulfide. However, the non-polar nature of the carbon material itself is destined to have a weak chemical interaction with the polar lithium polysulfide species. The problem of lithium polysulfide dissolving into the electrolyte and causing capacity loss still exists. The single use of physical blocking or chemical adsorption cannot completely inhibit the shuttle effect, and the effect on improving the overall performance of the battery is limited. At the same time, the polysulfide that inhibits the shuttle adsorption is not further converted. The continuously accumulated polysulfide will not only block the pores on the diaphragm, resulting in a weakened ability of the diaphragm to conduct ions, but also reduce the utilization rate of the active substance sulfur. Therefore, it is particularly important to give the diaphragm modification material the ability to catalyze the rapid redox conversion of polysulfide to subsequent products. It is necessary to develop a high-performance lithium-sulfur battery that can effectively inhibit the shuttle effect of polysulfide while having a catalytic effect on polysulfide, promote the catalytic conversion of polysulfide, further improve the utilization rate of sulfur, and improve the electrochemical performance of lithium-sulfur batteries. Summary of the invention

[0005] In order to solve the defects in the prior art, the present invention provides a high-performance lithium-sulfur battery, which includes a sulfur-carbon positive electrode, a lithium negative electrode, an electrolyte and a separator, wherein the separator includes a base film and a functional coating coated on one or both sides of the base film, and the functional coating includes molybdenum disulfide particles coated with metal molybdenum nanoparticles. Molybdenum disulfide has abundant surface active sites, can form strong chemical bonds with sulfur atoms in polysulfides, effectively adsorb and fix polysulfides, and prevent them from diffusing from the positive electrode to the negative electrode. Metal molybdenum nanoparticles have excellent catalytic activity, can accelerate the redox reaction of polysulfides, and promote their rapid conversion into solid Li2S, which not only improves the utilization rate of sulfur, but also reduces the accumulation of intermediate products, further inhibits the shuttle effect of polysulfides, and improves the coulombic efficiency and cycle stability of the battery. In addition, the presence of metal molybdenum nanoparticles can enhance the catalytic activity of MoS2 and further improve the conversion rate of polysulfides. In addition, metallic molybdenum nanoparticles have extremely high electrical conductivity. After being coated with molybdenum disulfide, they interact with MoS2 to form a synergistic effect, further improving the overall conductivity, forming an efficient conductive network, promoting the rapid transmission of electrons, and improving the battery's rate performance.

[0006] To achieve the above-mentioned object of the present invention, the present invention provides a high-performance lithium-sulfur battery, which includes a sulfur-carbon positive electrode, a lithium negative electrode, an electrolyte and a separator, wherein the separator includes a base film and a functional coating coated on one or both sides of the base film, and the functional coating includes molybdenum disulfide particles coated with metal molybdenum nanoparticles.

[0007] Furthermore, the base membrane is selected from one of a polyethylene membrane, a polypropylene membrane, a polyethylene / polypropylene double-layer membrane, a polypropylene / polyethylene / polypropylene three-layer membrane, a glass fiber membrane, and a PVDF-HFP porous membrane.

[0008] Preferably, the thickness of the functional coating is 1-10 μm. Preferably, the thickness of the functional coating is 3-8 μm, and more preferably, the thickness of the functional coating is 5 μm.

[0009] Furthermore, the functional coating is composed of polyvinylidene fluoride and molybdenum disulfide particles coated with metal molybdenum nanoparticles, wherein the mass ratio of the molybdenum disulfide particles coated with metal molybdenum nanoparticles to polyvinylidene fluoride is 8-10:1. The metal molybdenum nanoparticles themselves have extremely high electrical conductivity (about 1.7×10 7S / m), and MoS2 also exhibits a certain conductivity. After combining the two, an efficient conductive network can be formed, which further improves the overall conductivity, promotes the rapid transmission of electrons in it, and improves the rate performance of the battery. This allows the functional coating to achieve rapid electron transmission without the use of a conductive agent, which helps to improve the transmission rate of lithium ions in the separator, reduce additional interface resistance, and reduce the internal resistance of the entire system.

[0010] Furthermore, the preparation method of the molybdenum disulfide particles coated with metal molybdenum nanoparticles is as follows:

[0011] Step 1, preparing molybdenum disulfide particles: adding sodium molybdate dihydrate and thiourea to deionized water in turn, stirring and dissolving to obtain a mixed solution; heating the mixed solution to 60-80°C and keeping it warm for 4-6 hours, then transferring the mixed solution to a microwave reactor, performing microwave treatment, and then centrifugation drying to obtain MoS2 particle material;

[0012] Step 2, coating the molybdenum disulfide particles with metal molybdenum: prepare 1L of 0.05~0.1M sodium molybdate aqueous solution, add stabilizer polyvinyl pyrrolidone until it is completely dissolved; then add 100g of MoS2 particles prepared in step 1, and stir until they are evenly dispersed; slowly add 0.2mol of sodium borohydride thereto, stir thoroughly until it is completely dissolved to obtain a mixed solution, transfer the mixed solution to a stainless steel autoclave, react at 80°C for 3h, cool to room temperature, centrifuge, wash, dry and then grind into powder.

[0013] Furthermore, in step 1, the mass ratio of sodium molybdate dihydrate to thiourea is 1:2-2:1; and the microwave treatment conditions are 150-220° C., 10-20 min.

[0014] Furthermore, the diaphragm preparation method is as follows:

[0015] (1) adding molybdenum disulfide particles coated with metal molybdenum nanoparticles and polyvinylidene fluoride into an organic solvent and stirring them thoroughly to obtain a slurry;

[0016] (2) The slurry obtained in step (1) is evenly coated on one or both sides of the base film and vacuum dried to obtain a diaphragm.

[0017] Furthermore, the organic solvent is N-methylpyrrolidone, and the mass ratio of N-methylpyrrolidone to polyvinylidene fluoride is 20-50:1.

[0018] Furthermore, in the step (1), the stirring speed is 600-1000 r / min, and the stirring time is 1-3 h; in the step (2), the vacuum drying temperature is 60-90° C., and the drying time is 10-20 h.

[0019] Furthermore, the sulfur-carbon positive electrode is a graphene-sulfur composite positive electrode, and the electrolyte is a mixture of lithium bis(trifluoromethylsulfonyl)imide, lithium nitrate, 1,3-dioxolane and ethylene glycol dimethyl ether. The preparation method of the graphene-sulfur composite positive electrode is: sulfur and graphene are mixed in a mass ratio of 2:1 and placed in a ball mill, stirred at a speed of 600r / min for 10 hours; then placed in a nitrogen atmosphere and heat treated at 150°C for 8 hours to obtain the obtained product. The preparation method of the positive electrode is as follows: sampling according to the mass ratio of graphene-sulfur: Super P (conductive carbon): PVDF (binder) of 5:4:1 and mixing and grinding for 10 minutes, then adding a certain amount of N-methylpyrrolidone (NMP) as a solvent to make a slurry, and quickly grinding it to a uniform slurry with a bright surface and honey-like shape, and then using a scraper to apply it on a carbon-coated aluminum foil, and then transferring it to a vacuum oven at 60°C for 12 hours. After the electrode is dried, it is punched out using a 12mm mold of a punching machine for standby use.

[0020] Furthermore, the electrolyte was prepared as follows: 1 mol L -1 LiTFSI was used as lithium salt, and 0.1 mol L -1 LiNO3 is used as an additive and allowed to stand for 3 to 4 days until the solution is completely clarified for use.

[0021] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:

[0022] 1. The technical solution of the present invention is simple. It is the first time to propose the application of molybdenum disulfide particles coated with metal molybdenum nanoparticles in the functional layer of the lithium-sulfur battery separator, and to improve the battery performance by combining the advantages of the two materials. This composite material can not only effectively inhibit the shuttle effect of polysulfides, but also improve the conductivity and mechanical strength of the separator. Molybdenum disulfide (MoS2) has abundant surface active sites and can form strong chemical bonds with sulfur atoms in polysulfides, effectively adsorb and fix polysulfides, and prevent them from diffusing from the positive electrode to the negative electrode. This strong adsorption significantly reduces the shuttle effect of polysulfides and improves the Coulomb efficiency and cycle stability of the battery. Metal molybdenum nanoparticles have excellent catalytic activity and can accelerate the redox reaction of polysulfides and promote their rapid conversion to solid Li2S. This not only improves the utilization rate of sulfur, but also reduces the accumulation of intermediates, further inhibiting the shuttle effect of polysulfides. In addition, the presence of metal molybdenum nanoparticles can enhance the catalytic activity of MoS2, allowing it to play a greater role in the polysulfide conversion process;

[0023] 2. Metal molybdenum nanoparticles have extremely high electrical conductivity, and MoS2 also exhibits certain electrical conductivity. When the two are combined, an efficient conductive network can be formed, which significantly improves the conductivity, promotes the rapid transmission of electrons therein, and enhances the rate performance of the battery. Metal molybdenum nanoparticles can interact with MoS2 through electron tunneling effect or direct contact to form a synergistic dual conductive mechanism, further improving the overall conductivity of the functional coating, so that it has better charge transfer and lithium ion diffusion rate. At the same time, both metal molybdenum and MoS2 show good chemical stability in the electrolyte, and will not have side reactions with the solvent or lithium salt in the electrolyte, which improves the infiltration of the electrolyte in the battery, making the lithium-sulfur battery have better cycle performance and rate performance;

[0024] 3. Metal molybdenum nanoparticles have high hardness and mechanical strength, which can significantly enhance the mechanical properties of MoS2, prevent the diaphragm from deforming or rupturing during the charge and discharge process, maintain the integrity of the electrode structure, and extend the service life of the battery. At the same time, the presence of metal molybdenum nanoparticles can effectively buffer the volume expansion of sulfur during the charge and discharge process, help maintain good contact between the electrode and the diaphragm, and further improve the overall performance of the battery. It can also maintain stable physical and chemical properties under high temperature conditions, which is beneficial to the operation of lithium-sulfur batteries under high temperature conditions, prevent the diaphragm from softening or degrading at high temperatures, and ensure the safety and stability of the battery.

[0025] 4. The preparation method of the present invention has simple process, low raw material cost and is convenient for large-scale production. DETAILED DESCRIPTION

[0026] In order to make the technical problems solved by the present invention, the technical solutions adopted and the technical effects achieved clearer, the technical solutions of the embodiments of the present invention are further described in detail below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.

[0027] It should be noted that the reference to "embodiment" in this document means that the specific features, structures or characteristics described in conjunction with the embodiment may be included in at least one embodiment of the present application. The appearance of this phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0028] The experimental methods in the following examples are conventional methods unless otherwise specified. The materials, reagents, etc. used in the following examples are commercially available unless otherwise specified.

[0029] The performance test of the lithium-sulfur battery in the present invention is conducted by assembling a 2032 lithium-sulfur button battery, specifically: the lithium sheet is cut into a small disc with a diameter of 12 mm, the electrolyte is a 1,3-dioxolane / ethylene glycol dimethyl ether (DOL / DME, volume ratio of 1:1) solution containing 1 mol lithium bistrifluoromethylsulfonyl imide (LiTFSI) and 0.1 mol / L lithium nitrate (LiNO3), the prepared diaphragm is cut into a small disc with a diameter of 12 mm, and the positive electrode, diaphragm, negative electrode and electrolyte are assembled into a 2032 button battery. The specific assembly method is: the positive electrode is placed in the positive electrode shell, 100 mL of electrolyte is added, the diaphragm is placed, and then the negative electrode is placed on the diaphragm, and the gasket shrapnel and the negative electrode shell are added to the negative electrode in sequence, and finally the assembled battery is pressed together with the positive electrode shell and the negative electrode shell under a pressure of 50 MPa to obtain a 2032 button battery.

[0030] Example 1

[0031] A lithium-sulfur battery comprises a sulfur-carbon positive electrode, a lithium negative electrode, an electrolyte and a diaphragm, wherein the diaphragm is prepared by the following method:

[0032] (1) Preparation of MoS2 particles coated with metallic Mo nanoparticles:

[0033] Add sodium molybdate dihydrate and thiourea in a mass ratio of 1:2 into deionized water in turn, stir and dissolve to obtain a mixed solution; heat the mixed solution to 60°C and keep it warm for 4 hours, then transfer the mixed solution to a microwave reactor, microwave treat it at 150°C for 10 minutes, and then centrifuge and dry it to obtain MoS2 particulate material; prepare 1L of 0.05M sodium molybdate aqueous solution, add stabilizer polyvinyl pyrrolidone until it is completely dissolved; then add 100g of MoS2 particles prepared in step 1, stir until it is evenly dispersed; slowly add 0.2mol of sodium borohydride thereto, stir thoroughly until it is completely dissolved to obtain a mixed solution, transfer the mixed solution to a stainless steel autoclave, react at 80°C for 3 hours, cool to room temperature, centrifuge, wash, dry and grind into powder to obtain.

[0034] (2) Preparation of diaphragm: MoS2 particles coated with metal molybdenum nanoparticles and polyvinylidene fluoride in a mass ratio of 8:1 were added to N-methylpyrrolidone, where the mass ratio of N-methylpyrrolidone to polyvinylidene fluoride was 20:1, and the mixture was stirred at 600 r / min for 1 h to obtain a slurry; the obtained slurry was evenly coated on one side of a polyethylene diaphragm with a coating thickness of 1 μm, and vacuum dried at 60°C for 10 h to obtain a diaphragm.

[0035] The sulfur-carbon positive electrode preparation method is as follows: sulfur and graphene are mixed in a mass ratio of 2:1 and then placed in a ball mill, and stirred at a speed of 600r / min for 10 hours; then placed in a nitrogen atmosphere and heat treated at 150°C for 8 hours; samples are taken according to a mass ratio of graphene-sulfur: Super P: PVDF of 5:4:1 and mixed and ground for 10 minutes, and then a certain amount of N-methylpyrrolidone is added as a solvent to make a slurry, and after rapid grinding to a uniform slurry with a bright surface and honey-like shape, it is applied on a carbon-coated aluminum foil with a scraper, and then transferred to a vacuum oven at 60°C for baking for 12 hours. After the electrode is dried, it is punched out with a 12mm mold of a punching machine for standby use.

[0036] The lithium-sulfur battery using the above-mentioned separator and positive electrode was tested, and the first cycle discharge capacity was 1295 mAh g at a rate of 0.5C. -1 After 800 cycles, the capacity retention rate is 90.5%; the first cycle discharge capacity at a rate of 2C is 893mAhg -1 , the capacity retention rate is 84% ​​after 1000 cycles.

[0037] Example 2

[0038] A lithium-sulfur battery comprises a sulfur-carbon positive electrode, a lithium negative electrode, an electrolyte and a diaphragm, wherein the diaphragm is prepared by the following method:

[0039] (1) Preparation of MoS2 particles coated with metallic Mo nanoparticles:

[0040] Add sodium molybdate dihydrate and thiourea in a mass ratio of 2:1 into deionized water in turn, stir and dissolve to obtain a mixed solution; heat the mixed solution to 80°C and keep it warm for 6 hours, then transfer the mixed solution to a microwave reactor, microwave it at 220°C for 20 minutes, and then centrifuge and dry it to obtain MoS2 particulate material; prepare 1L of 0.1M sodium molybdate aqueous solution, add stabilizer polyvinyl pyrrolidone until it is completely dissolved; then add 100g of MoS2 particles prepared in step 1, stir until it is evenly dispersed; slowly add 0.2mol of sodium borohydride thereto, stir thoroughly until it is completely dissolved to obtain a mixed solution, transfer the mixed solution to a stainless steel autoclave, react at 80°C for 3 hours, cool to room temperature, centrifuge, wash, dry and grind into powder to obtain.

[0041] (2) Preparation of diaphragm: MoS2 particles coated with metal molybdenum nanoparticles and polyvinylidene fluoride in a mass ratio of 10:1 were added to N-methylpyrrolidone, where the mass ratio of N-methylpyrrolidone to polyvinylidene fluoride was 50:1, and the mixture was stirred at 1000 r / min for 3 h to obtain a slurry; the obtained slurry was evenly coated on one side of a polypropylene diaphragm with a coating thickness of 10 μm, and vacuum dried at 90°C for 20 h to obtain a diaphragm.

[0042] The method for preparing the sulfur-carbon positive electrode is the same as that in Example 1.

[0043] The lithium-sulfur battery using the above-mentioned separator and positive electrode was tested, and the first cycle discharge capacity was 1269 mAh g at a rate of 0.5C. -1 After 800 cycles, the capacity retention rate is 92.6%; the first cycle discharge capacity at a rate of 2C is 872mAhg -1 , the capacity retention rate is 88% after 1000 cycles.

[0044] Example 3

[0045] A lithium-sulfur battery comprises a sulfur-carbon positive electrode, a lithium negative electrode, an electrolyte and a diaphragm, wherein the diaphragm is prepared by the following method:

[0046] (1) Preparation of MoS2 particles coated with metallic Mo nanoparticles:

[0047] Add sodium molybdate dihydrate and thiourea in a mass ratio of 1:1 into deionized water in turn, stir and dissolve to obtain a mixed solution; heat the mixed solution to 70°C and keep it warm for 5 hours, then transfer the mixed solution to a microwave reactor, microwave treat it at 180°C for 15 minutes, and then centrifuge and dry it to obtain MoS2 particulate material; prepare 1L of 0.08M sodium molybdate aqueous solution, add stabilizer polyvinyl pyrrolidone until it is completely dissolved; then add 100g of MoS2 particles prepared in step 1, stir until it is evenly dispersed; slowly add 0.2mol of sodium borohydride thereto, stir thoroughly until it is completely dissolved to obtain a mixed solution, transfer the mixed solution to a stainless steel autoclave, react at 80°C for 3 hours, cool to room temperature, centrifuge, wash, dry and grind into powder to obtain.

[0048] (2) Preparation of diaphragm: MoS2 particles coated with metal molybdenum nanoparticles and polyvinylidene fluoride in a mass ratio of 9:1 were added to N-methylpyrrolidone, where the mass ratio of N-methylpyrrolidone to polyvinylidene fluoride was 30:1, and the mixture was stirred at 800 r / min for 2 h to obtain a slurry; the obtained slurry was evenly coated on both sides of a polyethylene / polypropylene double-layer diaphragm, with a single-side coating thickness of 5 μm, and the diaphragm was obtained by vacuum drying at 80°C for 15 h.

[0049] The method for preparing the sulfur-carbon positive electrode is the same as that in Example 1.

[0050] The lithium-sulfur battery using the above-mentioned separator and positive electrode was tested, and the first cycle discharge capacity was 1277mAh g at a rate of 0.5C. -1 After 800 cycles, the capacity retention rate is 91.7%; at a rate of 2C, the first cycle discharge capacity is 879mAhg -1, the capacity retention rate after 1000 cycles is 85.3%.

[0051] Comparative Example 1

[0052] A lithium-sulfur battery comprises a sulfur-carbon positive electrode, a lithium negative electrode, an electrolyte and a diaphragm, wherein the diaphragm is prepared by the following method:

[0053] (1) Preparation of molybdenum disulfide particles:

[0054] Sodium molybdate dihydrate and thiourea in a mass ratio of 1:1 are sequentially added into deionized water, stirred and dissolved to obtain a mixed solution; the mixed solution is heated to 70°C and kept warm for 5 hours, then the mixed solution is transferred to a microwave reactor, microwave-treated at 180°C for 15 minutes, then centrifugally dried, and ground into powder to obtain the product.

[0055] (2) Preparation of diaphragm: MoS2 particles and polyvinylidene fluoride in a mass ratio of 9:1 were added to N-methylpyrrolidone (the mass ratio of N-methylpyrrolidone to polyvinylidene fluoride was 30:1), and the mixture was stirred at 800 r / min for 2 h to obtain a slurry; the obtained slurry was evenly coated on both sides of a polyethylene / polypropylene double-layer diaphragm, with a single-side coating thickness of 5 μm; the diaphragm was vacuum dried at 80°C for 15 h to obtain a diaphragm.

[0056] The method for preparing the sulfur-carbon positive electrode is the same as that in Example 1.

[0057] The lithium-sulfur battery using the above-mentioned separator and positive electrode was tested, and the first cycle discharge capacity was 1245 mAh g at a rate of 0.5C. -1 After 800 cycles, the capacity retention rate is 73.5%; the first cycle discharge capacity at a rate of 2C is 847mAhg -1 , the capacity retention rate after 1000 cycles is 62.9%.

[0058] Comparative Example 2

[0059] A lithium-sulfur battery comprises a sulfur-carbon positive electrode, a lithium negative electrode, an electrolyte and a diaphragm, wherein the diaphragm is a commercial PVDF-HFP porous membrane, and the preparation method of the sulfur-carbon positive electrode is the same as that of Example 1.

[0060] The lithium-sulfur battery with commercial PVDF-HFP porous membrane and sulfur-carbon cathode was tested, and the first cycle discharge capacity was 1201 mAh g at a rate of 0.5C. -1 After 800 cycles, the capacity retention rate was 46.2%; at a rate of 2C, the first cycle discharge capacity was 763mAh g -1 , the capacity retention rate is 31.8% after 1000 cycles.

[0061] Comparative Example 3

[0062] A lithium-sulfur battery comprises a sulfur-carbon positive electrode, a lithium negative electrode, an electrolyte and a diaphragm, wherein the diaphragm is prepared by the following method:

[0063] (1) Preparation of MoS2 particles coated with metallic Mo nanoparticles:

[0064] Add sodium molybdate dihydrate and thiourea in a mass ratio of 1:1 into deionized water in turn, stir and dissolve to obtain a mixed solution; heat the mixed solution to 70°C and keep it warm for 5 hours, then transfer the mixed solution to a microwave reactor, microwave treat it at 180°C for 15 minutes, and then centrifuge and dry it to obtain MoS2 particulate material; prepare 1L of 0.16M sodium molybdate aqueous solution, add stabilizer polyvinyl pyrrolidone until it is completely dissolved; then add 100g of MoS2 particles prepared in step 1, stir until it is evenly dispersed; slowly add 0.3mol of sodium borohydride thereto, stir thoroughly until it is completely dissolved to obtain a mixed solution, transfer the mixed solution to a stainless steel autoclave, react at 120°C for 3 hours, cool to room temperature, centrifuge, wash, dry and grind into powder to obtain.

[0065] (2) Preparation of diaphragm: MoS2 particles coated with metal molybdenum nanoparticles and polyvinylidene fluoride in a mass ratio of 7:1 were added to N-methylpyrrolidone, where the mass ratio of N-methylpyrrolidone to polyvinylidene fluoride was 20:1, and the mixture was stirred at 800 r / min for 2 h to obtain a slurry; the obtained slurry was evenly coated on both sides of a polyethylene / polypropylene double-layer diaphragm, with a single-side coating thickness of 12 μm. The diaphragm was then vacuum dried at 80°C for 15 h to obtain a diaphragm.

[0066] The method for preparing the sulfur-carbon positive electrode is the same as that in Example 1.

[0067] The lithium-sulfur battery using the above-mentioned separator and positive electrode was tested, and the first cycle discharge capacity was 1210 mAh g at a rate of 0.5C. -1 After 800 cycles, the capacity retention rate is 72.5%; at a rate of 2C, the first cycle discharge capacity is 810mAhg -1 , the capacity retention rate after 1000 cycles is 55.8%.

[0068] It can be seen from the above test data that the discharge capacity of the lithium-sulfur battery using the specific diaphragm and positive electrode of the present invention remains at a relatively high value when the current density increases to 2C. When the rate is switched back to a low rate, the discharge capacity of the lithium-sulfur battery can be quickly restored, and the battery has excellent reversibility. In addition to excellent rate performance, the lithium-sulfur battery using the specific diaphragm and positive electrode of the present invention exhibits excellent cycle performance at both 0.5C and 2C. After 1000 cycles at 2C, the capacity remains above 84%, and after 800 cycles at 0.5C, the capacity remains above 90%. It can be seen that the lithium-sulfur battery of the present invention has excellent cycle stability.

[0069] The above is a detailed description of a high-performance lithium-sulfur battery. The above content is a further detailed description of the present invention in combination with a specific preferred embodiment. It cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, without departing from the concept of the present invention, its architecture can be flexible and can derive a series of products. Just making a few simple deductions or substitutions should be regarded as belonging to the scope of patent protection determined by the submitted claims of the present invention.

Claims

1. A high-performance lithium-sulfur battery, comprising a sulfur-carbon positive electrode, a lithium negative electrode, an electrolyte and a separator, characterized in that: The diaphragm comprises a base film and a functional coating coated on one or both sides of the base film, wherein the functional coating comprises molybdenum disulfide particles coated with metal molybdenum nanoparticles.

2. The lithium-sulfur battery according to claim 1, characterized in that: The base film is selected from one of a polyethylene membrane, a polypropylene membrane, a polyethylene / polypropylene double-layer membrane, a polypropylene / polyethylene / polypropylene three-layer membrane, a glass fiber membrane, and a PVDF-HFP porous membrane.

3. The lithium-sulfur battery according to claim 1, characterized in that: The thickness of the functional coating is 1-10 μm.

4. The lithium-sulfur battery according to claim 1, characterized in that: The functional coating consists of polyvinylidene fluoride and molybdenum disulfide particles coated with metal molybdenum nanoparticles, wherein the mass ratio of the molybdenum disulfide particles coated with metal molybdenum nanoparticles to polyvinylidene fluoride is 8-10:

1.

5. The lithium-sulfur battery according to claim 1, characterized in that: The preparation method of the molybdenum disulfide particles coated with metal molybdenum nanoparticles is as follows: Step 1, preparing molybdenum disulfide particles: adding sodium molybdate dihydrate and thiourea to deionized water in turn, stirring and dissolving to obtain a mixed solution; heating the mixed solution to 60-80°C and keeping it warm for 4-6 hours, then transferring the mixed solution to a microwave reactor, performing microwave treatment, and then centrifugation drying to obtain MoS2 particle material; Step 2, coating the molybdenum disulfide particles with metal molybdenum: prepare 1L of 0.05~0.1M sodium molybdate aqueous solution, add stabilizer polyvinyl pyrrolidone until it is completely dissolved; then add 100g of MoS2 particles prepared in step 1, and stir until they are evenly dispersed; slowly add 0.2mol of sodium borohydride thereto, stir thoroughly until it is completely dissolved to obtain a mixed solution, transfer the mixed solution to a stainless steel autoclave, react at 80°C for 3h, cool to room temperature, centrifuge, wash, dry and then grind into powder.

6. The lithium-sulfur battery according to claim 5, characterized in that: In step 1, the mass ratio of sodium molybdate dihydrate to thiourea is 1:2-2:1; and the microwave treatment conditions are 150-220° C., 10-20 min.

7. The lithium-sulfur battery according to claim 1, characterized in that: The diaphragm preparation method is as follows: (1) adding molybdenum disulfide particles coated with metal molybdenum nanoparticles and polyvinylidene fluoride into an organic solvent and stirring them thoroughly to obtain a slurry; (2) The slurry obtained in step (1) is evenly coated on one or both sides of the base film and vacuum dried to obtain a diaphragm.

8. The lithium-sulfur battery according to claim 7, characterized in that: The organic solvent is N-methylpyrrolidone, and the mass ratio of N-methylpyrrolidone to polyvinylidene fluoride is 20-50:

1.

9. The lithium-sulfur battery according to claim 7, characterized in that: In the step (1), the stirring speed is 600-1000 r / min, and the stirring time is 1-3 h; in the step (2), the vacuum drying temperature is 60-90° C., and the drying time is 10-20 h.

10. The lithium-sulfur battery according to claim 1, characterized in that: The sulfur-carbon positive electrode is a graphene-sulfur composite positive electrode, the electrolyte is a mixture of lithium bis(trifluoromethylsulfonyl)amide, lithium nitrate, 1,3-dioxolane and ethylene glycol dimethyl ether, and the preparation method of the graphene-sulfur composite positive electrode is: sulfur and graphene are mixed in a mass ratio of 2:1 and placed in a ball mill, stirred at a speed of 600r / min for 10 hours; then placed in a nitrogen atmosphere and heat treated at 150°C for 8 hours to obtain the obtained product.

Citation Information

Patent Citations

  • Spherical hollow cerium oxide modified diaphragm for lithium-sulfur battery and preparation method thereof as well as lithium-sulfur battery with diaphragm

    CN105977434A

  • Cobalt-doped carbon nanotube composite diaphragm and preparation method thereof

    CN112290162A

  • High-activity Mn / Co-N double-site doped carbon material catalyst, preparation method and application thereof

    CN114068935A

  • Rare earth monatomic material, preparation method thereof and application of rare earth monatomic material as lithium-sulfur battery diaphragm modified material

    CN114976474A

  • Preparation method of high-entropy monatomic catalyst modified diaphragm and application of high-entropy monatomic catalyst modified diaphragm in lithium-sulfur battery

    CN117335094A